KONJUNGSI KOORDINATIF DALAM TAUSYIAH USTADZ MUHAMMAD NUR MAULANA PADA ACARA ISLAM ITU INDAH BULAN JANUARI 2019 - Reza Melliadona; Sainil Amral; Supriyati Supriyati (Universitas Batanghari, 2021)
The purpose of this research is to describe the form of coordinating conjunction in the Tausyiah Ustadz Muhammad Nur Maulana on the talkshow Islam Itu Indah January 2019. This type of research is descriptive with qualitative method. The data is in the form of Tausyiah Ustadz Muhammad Nur Maulana quotes on the talkshow Islam Itu Indah January 2019 containing coordinating conjunctions. Data collection techniques are performed by recording, transcribing, marking, identifying, and grouping data. The data in the analysis uses discourse analysis by applying the concept of Rahardi, as well as analysis techniques using the concept of Miles and Hubermen. The results of research on the form of coordinating conjunction on the talkshow Ustadz Muhammad Nur Maulana include 59 quotations containing 4 forms. The 4 forms are 1) additive conjunction, 2) adversative conjunction, 3) alternative conjunction, 4) conclusion conjunction.